1991
DOI: 10.1111/j.1471-0528.1991.tb10372.x
|View full text |Cite
|
Sign up to set email alerts
|

Crouching over the toilet seat: prevalence among British gynaecological outpatients and its effect upon micturition

Abstract: This study investigated whether British women prefer to crouch over public toilet seats, and measured the effect of such a voiding position on urine flow rate and residual urine volume. Of 528 consecutive women who attended a general gynaecological clinic and completed an anonymous questionnaire, 85% usually crouched over the toilet when using a public convenience, 12% applied paper to the seat and 2% sat directly on public toilet seats. When using a friend's bathroom 38% of the women voided by crouching. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 2 publications
2
37
2
Order By: Relevance
“…The use of modern uroflowmeters with the levels of accuracy cited above is assumed. Sitting rather than crouching to void gives a better urine flow [16].…”
Section: Introductionmentioning
confidence: 99%
“…The use of modern uroflowmeters with the levels of accuracy cited above is assumed. Sitting rather than crouching to void gives a better urine flow [16].…”
Section: Introductionmentioning
confidence: 99%
“…In some countries, it is traditional for men to void in the sitting position. Furthermore, up to 85% of women prefer to void in a crouching position when using a public toilet (1). Some bedridden patients have to void in either a sitting or recumbent position for medical reasons.…”
mentioning
confidence: 99%
“…Some bedridden patients have to void in either a sitting or recumbent position for medical reasons. For these patients, management of neuro-urological problems causing post-void residual (PVR) urine and insufficient emptying is very important in order to prevent significant urinary problems such as urinary tract infections and bladder stones, as it has been reported that the PVR urine volume is affected by voiding position (1,2). However, in a previous study (3), we demonstrated that there were no statistically significant differences in PVR between two voiding positions for patients with lower urinary tract symptoms (LUTS) suggestive of benign prostatic hyperplasia (BPH).…”
mentioning
confidence: 99%
“…These differences could be explained in two ways: a device-related artifact, time for urine to pass through the P-Mate with additional friction, or inadequate pelvic floor muscle (PFM) relaxation. This inadequate PFM relaxation could be related either to an unusual voiding position for women, causing surprise at these trials, or to adductive muscle contraction in an inadequate position, namely, bent knees [1,8]. To maintain a standing position with bent knees, there is need for a concurrent contraction of hip adductor and gluteal muscles, which is known to induce a synergic contraction of the PFM and urethral sphincter [8].…”
Section: Resultsmentioning
confidence: 99%
“…Since women, from school age to elderly, have to face hygienic concerns in public bathrooms or discomfort and fear being seen urinating outdoors, they develop coping micturition behaviors: infrequent voiding, crouching over the toilet bowl instead of sitting on it, and abdominal straining to shorten time spent in the toilets [1,2]. Recurrent urinary tract infections, chronic retention, and other voiding dysfunctions have been associated with such micturition behaviors [3,4].…”
Section: Introductionmentioning
confidence: 99%